2017
DOI: 10.1111/acv.12390
|View full text |Cite
|
Sign up to set email alerts
|

Use of agricultural land by breeding waders in low‐intensity farming landscapes

Abstract: Agriculture is one of the primary threats to biodiversity but agricultural land can also provide key resources for many species and, in some parts of the world, agricultural land supports important populations of species of conservation concern. In these cases, it is important to understand species' use of agricultural land before further expansion or intensification of agricultural activities occurs. Agriculture in Iceland is still relatively low in intensity and extent, and internationally important populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…2005, Jóhannesdóttir et al. 2018, 2019). However, the level of nest predation (̃40% of nests predated) in our study is similar to levels found across all geographical regions for ground‐nesting waders (MacDonald & Bolton 2008, Roodbergen et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2005, Jóhannesdóttir et al. 2018, 2019). However, the level of nest predation (̃40% of nests predated) in our study is similar to levels found across all geographical regions for ground‐nesting waders (MacDonald & Bolton 2008, Roodbergen et al.…”
Section: Discussionmentioning
confidence: 97%
“…These landscapes comprise large areas of semi‐natural habitats interspersed with agricultural land (primarily for livestock grazing and hayfields; Jóhannesdóttir et al. 2018, 2019). At these subarctic latitudes (63°–66°N) the growing season is very short, with both the onset of vegetation growth and the rate of growth being highly temperature‐dependent (Thorvaldsson et al.…”
mentioning
confidence: 99%
“…The subspecies of black‐tailed godwits breeding on Iceland ( Limosa l. islandica ) also faces warming springs and agricultural intensification (Gill et al., ; Jóhannesdóttir, Alves, Gill, & Gunnarsson, ), but spring warming at this more northern latitude and the relative low level of agricultural intensification so far seems to have benefitted the birds. The Icelandic black‐tailed godwits seem to be more flexible in general; laying dates within pairs were not repeatable and advanced by 2.5 days per year (and 4 day/°C June temperature) during the last 11‐year period, but little is known about how individual arrival affects laying date in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The divergent tectonic plate boundary that crosses Iceland along the North-Atlantic ridge, originates frequent volcanic eruptions (Arnalds 2015), and patterns of spatial variation in wader density are positively correlated with the amount of volcanic dust deposition. Deposition rates vary on a SW-NE axis through Iceland and regional variation in wader abundance is apparent along this axis, likely caused by the fertilizing effect of the dust input, particularly in wetlands (Gunnarsson et al 2015, Jóhannesdóttir et al 2018. Volcanic activity can have extreme effects on ecosystems as a whole, altering landscapes and even changing average temperatures.…”
Section: Distributionmentioning
confidence: 99%